ОСТРЫЙ КОРОНАРНЫЙ СИНДРОМ: КОМПЛЕКСНЫЙ ВЗГЛЯД НА ПРОБЛЕМУ, ЗНАЧЕНИЕ ГОСПИТАЛЬНОГО И АМБУЛАТОРНОГО ЭТАПОВ ЛЕЧЕНИЯ ПАЦИЕНТОВ - И. С. Скопец; Н. Н. Везикова; И. М. Марусенко; А. Н. Малыгин (Архивъ внутренней медицины, 2012)
The article is devoted to one of the topical issues of contemporary health care — acute coronary syndrome (ACS). The objective of the study was to evaluate patients who were treated at the Regional Vascular Center during the hospital phase of treatment and to analyze treatment during the outpatient. Besides, the article analyses patients’ compliance, long-term clinical and social consequences of acute coronary syndrome.